Continuidad del negocio: conceptualización y metodologías de evaluación (2021)
Business continuity is the current challenge for organizations since they have to face increasing demands in dynamic environments. Companies are exposed to different situations such as failures, natural disasters, attacks, economic crises, among others, which leads to a proactive approach to protect the business from such effects. Therefore, strategies such as Business Continuity Management (BCM) have been created, which is considered a way to incorporate the recovery process within the preventive framework of the organization risk assessment (Timms, 2018; Zeng & Zio, 2017). From the point of view of the International Organization for Standardization - ISO, business continuity is the capacity of organizations to sustain themselves before internal and external risks that may affect their permanence in the market, as well as to continue with their offer within a set time sustainedly (International Organization for Standardization, 2019).